Rosa roxburghii fermented juice mitigates LPS-induced acute lung injury by modulation of intestinal flora and metabolites - Chen, Zhiyu; Zhang, Shuo; Sun, Xiaodong; Meng, Duo; Lai, Chencen; Zhang, Min; Wang, Pengjiao; Huang, Xuncai; Gao, Xiuli (Frontiers in Microbiology, 2024)
Acute lung injury (ALI) is a severe pulmonary condition with high mortality and morbidity, lacking effective pharmacotherapeutic options. Rosa roxburghii Tratt, a unique fruit from southwestern China, is valued for its rich nutritional content and functional properties. Fermentation is known to enhance the nutritional value, flavor, and shelf life of foods. In this study, we investigated the effects of fermented Rosa roxburghii juice (RRFJ) on gut microbiota, metabolites, and the levels of short-chain fatty acids in the intestines, as well as its impact on lung tissue and intestine tissue injury, inflammation, and oxidative stress in murine models. The results showed that RRFJ modulated gut microbiota and metabolites, increased short-chain fatty acid levels, and consequently reduced lung tissue injury, inflammation, and oxidative stress in mice with ALI. These findings suggest that RRFJ has the potential to serve as a functional dietary adjunct in the management of acute lung injury, providing a scientific basis for its therapeutic role.